1993
DOI: 10.2105/ajph.83.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases in a Canadian Arctic population.

Abstract: IntrodudionRecent reports from several indigenous Arctic populations in Greenland1 and Alaska2 have indicated that the mortality risk from ischemic heart disease is substantially below that of the non-Native population. The risk for cerebrovascular disease, on the other hand, either exceeds' or is not signifcantly different from that of non-Natives.2 Etiologic hypotheses that have been proposed to account for the observed pattern include dietary factors, particularly the consumption of marinemammal-based omega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 18 publications
(1 reference statement)
3
50
0
4
Order By: Relevance
“…47 The difference in the MetS rates between two Aboriginal groups may be due to a greater maintenance of traditional lifestyle and diet in Inuit people 11,48 compared to Native Indians, who have had a much longer and more extensive exposure to western influence. 47 A report from SLHDP suggested that a higher consumption of processed foods and 'fast food' was associated with an increased risk of obesity and diabetes in the Oji-Cree community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 The difference in the MetS rates between two Aboriginal groups may be due to a greater maintenance of traditional lifestyle and diet in Inuit people 11,48 compared to Native Indians, who have had a much longer and more extensive exposure to western influence. 47 A report from SLHDP suggested that a higher consumption of processed foods and 'fast food' was associated with an increased risk of obesity and diabetes in the Oji-Cree community.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Low CVD mortality rates were found among Aboriginal populations in Canada compared with general populations prior to 1980s. 10,11 However, with significant social, economic, and cultural changes over the past several decades, Aboriginal people have been undergoing a health transition, with declining rates of communicable diseases and increasing chronic illnesses. Obesity and type 2 diabetes have reached an epidemic stage in some Canadian Aboriginal communities.…”
Section: Introductionmentioning
confidence: 99%
“…2 In these indigenous communities there was a significant female predominance because a large proportion of young males had occupational migration so, comparative to urban areas, the indigenous communities have a modified population structure. 11,13 There are few reports about the prevalence of hypertension and its association with cardiovascular risk factors in ethnic minority groups of traditional communities, 10,[14][15][16][17] and is virtually unknown in Latin American traditional-living populations. The epidemiological pattern of the cardiovascular risk profile in the indigenous people of traditional communities differs from that among inhabitants of partly westernised or westernised urban societies, 14 and thus provide an attractive population for examining the natural history of hypertensive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown signi®cant differences between the Inuit and American or European White populations with regard to risk factors for cardiovascular disease, in particular differences in plasma lipids and a lower prevalence of diabetes among the Inuit (Bang & Dyerberg, 1981;Schraer et al, 1988;Young et al, 1992Young et al, , 1993Young et al, , 1995Bjerregaard et al, 1997). Genetic factors, diet and other environmental factors are likely to play a role in the observed differences in plasma lipids and diabetes.…”
Section: Introductionmentioning
confidence: 99%